Progressives, patterns, pedagogy : a corpus-driven approach to English progressive forms, functions, contexts, and didactics - Römer, Ute (Studies in corpus linguistics ;, 2005)
This book presents a large-scale corpus-driven study of progressives in 'real' English and 'school' English, combining an analysis of general linguistic interest with a pedagogically motivated one. A systematic comparative analysis of more than 10,000 progressive forms taken from the largest existing corpora of spoken British English and from a small corpus of EFL textbook texts highlights numerous differences between actual language use and textbook language concerning the distribution of progressives, their preferred contexts, favoured functions, and typical lexical-grammatical patterns. On.